Surgical Management of Wild-Type Gastrointestinal Stromal Tumors: A Report From the National Institutes of Health Pediatric and Wildtype GIST Clinic - Weldon, Christopher B. (J Clin Oncol, 2017)
PURPOSE: Wild-type gastrointestinal stromal tumors (WT-GISTs) that lack KIT or PDGFRA mutations represent a unique subtype of GIST that predominantly affects children. We sought to determine the effect on event-free survival (EFS) of staging variables, extent of resection, and repeat resection of tumors. METHODS: In 2008, a WT-GIST clinic was established at the National Cancer Institute, allowing the development of a large clinical database. We included participants who underwent resection of WT-GIST. Associations with EFS (ie, freedom from disease progression or recurrence) were evaluated using the Kaplan-Meier method and Cox proportional hazards modeling. RESULTS: Among 76 participants with WT-GISTs, the median follow-up was 4.1 years. Overall EFS (± SE) was 72.6 ± 5.4% at 1 year, 57.6 ± 6.2% at 2 years, 23.7 ± 6.0% at 5 years, and 16.3 ± 5.5% at 10 years postoperatively. Hazard of disease progression or recurrence was significantly increased for patients with metastatic disease (adjusted hazard ratio [AHR], 2.3; 95% CI, 1.0 to 5.1; P = .04) and > 5 mitoses per 50 high-power fields (AHR, 2.5; 95% CI, 1.1 to 6.0; P = .03), whereas there was no significant effect of negative microscopic resection margins (AHR, 0.9; 95% CI, 0.4 to 2.2; P = 0.86). There was no association between type of gastric resection (ie, anatomic v partial/wedge) and EFS (P = .67). Repeated resection after the initial resection was significantly associated with decreasing postoperative EFS (P < .01). Five patients (6%) died after initial enrollment in 2008. CONCLUSION: WT-GIST is an indolent disease, and most patients survive with disease progression. We found no improvement in EFS with more extensive or serial resections. Disease progression or recurrence may be more closely related to tumor biology than surgical management. These data suggest that resections for WT-GISTs be restricted to the initial procedure and that subsequent resections be performed only to address symptoms such as obstruction or bleeding.